Weed extracts as biocontrol agents for management of black pod on cocoa / Nor Amerulah Nor Mohamad - Nor Mohamad, Nor Amerulah (Faculty of Plantation and Agrotechnology, 2018)
In Malaysia, cocoa had become the third major crop and the crop for agricultural diversification. Cocoa production are mostly disturbed by the infection of the fungal diseases and from all the disease that infect, black pod was the one that giving most economically serious problem toward cocoa industry in Malaysia. Black pod disease of cocoa in Malaysia is commonly associated with attack from fungus Phytophora palmivora. Some local farmers were too dependent on the chemical fungicide to control the disease. In continuous, methods of controlling by using chemicals can be expensive and sometimes ineffective. The uses of plant extracts to control black pod disease on cocoa were one of the environmentally friendly controls which can reduce and avoid negative impact on human and beneficial microbes. Thus the objectives of these studies were to induce growth and reproduction of Phytophthora species on Potato Dextrose Agar (PDA) and Tomato Juice Agar (TJA) and to determine antifungal activity of some weed crude extract against control of black pod on cocoa. In consequences, 10 weed species were collected randomly to be extracted and will undergo food poisoning technique. Next, from the entire weed extracts that been tested, there was a weed species which was Solanum torvum that can control the growth and development of Phytophthora pod rot disease in vitro experiment. It shows some positive results which the colony of Solanum torvum extracts were much smaller than the negative control. Thus it can be concluded that there was a weed species that can control Phytophthora pod rot disease.